The Global Histories of Books
X, 334 p. 13 illus.
Keywords: “In this smart, wide-ranging study of texts on the move, the global history of the book becomes a counter-history of the nation. Rather than pitting one against the other, contributors show how entangled these spheres are – and how key print culture is to illuminating points of convergence and divergence. Moving skillfully between dog-eared volumes and the booksellers, readers and marketplaces that made them, this collection brims with insights about the lives of books and their role not simply in reflecting global relations but in creating them -- with every turn of the page.” — Antoinette M. Burton, Professor of History, University of Illinois, USA, and co-author with Isabel Hofmeyr of Ten Books that Shaped the British Empire. This collection is an edited volume of essays that showcases how books played a crucial role in making and materialising histories of travel, scientific exchanges, translation, and global markets from the late-eighteenth century to the present. While existing book historical practice is overly dependent on models of the local and the national, we suggest that approaching the book as a cross-region, travelling – and therefore global- object offers new approaches and methodologies for a study in global perspective. By thus studying the book in its transnational and inter-imperial, textual, inter-textual and material dimensions, this collection will highlight its key role in making possible a global imagination, shaped by networks of print material, readers, publishers and translators.